Assessment of motivation, expectations and satisfaction of adult patients submitted to orthodontic treatment - Patrícia Gomide de Souza Andrade Oliveira; Rubens Rodrigues Tavares; Jairo Curado de Freitas (Dental Press Editora, 2013)
OBJECTIVE: The purpose of this study was to analyze the psychological aspects of adult patients who sought and underwent orthodontic treatment, evaluating their expectations and discomfort during treatment, as well as their satisfaction after completion of dental movement. RESULTS AND CONCLUSIONS: Data obtained from previous published papers, and also from questionnaires answered by 54 patients, showed that adult patients stood out for their attention to details and high interest in the esthetic improvements provided by treatment, and also for a greater perception of their initial malocclusion. On the other hand, the same data showed that adult patients, once informed about the limitations of their treatment and having confidence on the orthodontist, presented a high level of satisfaction with treatment results, revealing themselves as good patients for indication and execution of orthodontic procedures.